Perception of customers on the most important criteria to be effective salesperson in TPM Technopark Sdn Bhd / Mohamad Zaini Ibrahim - Ibrahim, Mohamad Zaini (Faculty of Business and Management, 2011)
Salesperson one of important person who influencing, informing, or persuading a potential buyer's purchasing decision. Therefore the salesperson’s characteristic is very important to give best impression towards customers. So the correct criteria or characteristic should be determined in order to be effective salesperson and indirectly to increase sale performance. Besides that, these correct criteria can have a wide range of objectives, including: sales increases, new product acceptance, creation of brand equity, positioning, competitive retaliations, or creation of a corporate image. The research title “Perception of Customers on The Most Important Criteria To Be Effective Salesperson in TPM Technopark Sdn Bhd” had been conducted to obtain the results at TPM Technopark Sdn Bhd. This research has been answered by 80 respondents through questionnaire. Instead of it, the Statistical Package for the Social Science (SPSS) version 18.0 has been used to summarize the data. Based on this research, the result indicates knowledge is the elements that contribute most in be good salesperson. Besides that, results shows there are significant relationship between all the independent variables with dependent variable. As a conclusion, the results of the findings that include the analysis of the demographic profile, and elements that contribute in be good salesperson. For the recommendation of this study made based on several logical factors and impact of current situation to salesperson practiced.